Kapabilitas Kampus Dalam Pengembangan Manajemen Sumber Daya Manusia (MSDM) Sebagai Wadah Mewujudkan Keahlian Mahasiswa - Saputra, Andrian (IJMA (Indonesian Journal of Management and Accounting), 2023)
This study discusses the topic of Human Resource Management and Skills, with a focus on the role of higher education institutions in optimizing and enhancing students' skills in management and organization. The aim is to find out the extent of the correlation between campus and HRM. The research method was carried out using a library literacy approach. Management of resources that are managed in order to oversee human resources in the lecture environment. By all means and efforts of human resources available in organizations/agencies it is very important to define all potential students who have an impact on organizational and campus efforts to achieve goals. The concept of human resource management on campus will provide insight into shaping quality and play an important role in building the image of the best quality graduates. Human resource management on campus can also be the driving force for creating faculty enthusiasm along with the faculty's courage to face it. The prospect is positive and provides something useful for the development of education. as well as for the environment in which they are located, so that the existence of lecturers and students is expected to remain a light and role model as academics who are able to change the mindset of society so that they develop and progress along with the development of the modern era. Through efforts to acquire skills as academics and knowledge.